Sustainable regional development from the perspective of economic resilience: Based on the impact of COVID-19 - Aotian Peng (PLoS ONE, 2025)
The process of regional economic development is marked by a sustained exposure to external disturbances. In today’s unpredictable and tumultuous global environment, such disturbances have become increasingly common, underlining the need to advance a region’s economic resilience and foster adaptive mechanisms to handle environmental flux. Comparing the typical provinces in eastern, central, western and northeastern regions during the COVID-19 epidemic period, it found that the economic resilience performance of Henan Province, which is a representative of the central region, has the following characteristics. Henan Province has the lowest total production resilience in the selected regions, but it is in the second position in terms of development potential resistance, while it is in the middle range in terms of resilience performance, and it has a weaker resistance performance in terms of the resilience indicator of the standard of living of the residents. Against this backdrop, this study undertakes an analysis and comparison of the economic resilience indicators of the 18 cities in Henan Province to suggest several refinements. It urges a promotion of the integrated development of the primary, secondary, and tertiary industries through increasing emphasis on the industrial sector, which will enable a transformation of the sectoral structuring. Further, digitization can help the upgrading of industries’ intelligence and function as a lever to raise their competitiveness. Innovation in enterprises is also crucial in enhancing industrial competitiveness, by bolstering the technological innovation capabilities of enterprises and simultaneously boosting the wage-based incomes of residents, resulting in an overall improvement in their standard of living. Also, the study emphasizes the establishment of a digital talent platform to construct a sound regional talent ecology system.